Evaluating the Role of Psychological Pricing Techniques in Shaping Consumer Perception and Purchase Intent in Grocery Retail - Vega, Noemi C.; Manlapaz, Janella G.; Manalastas, Patricia L.; Y. Mesina, Ron Christian; Sansano, Nadine R. (International Journal of Sustainability and Advanced Integrated Research, 2025)
This study investigates the influence of psychological pricing strategies on consumer behavior in the grocery retail sector. Using a descriptive quantitative research design, data were gathered through structured surveys examining consumer responses to charm pricing, product bundling, and discount promotions. The findings reveal strong consumer agreement that psychological pricing enhances perceived affordability, encourages impulse buying, and affects long-term purchasing patterns. Respondents, particularly younger and price-sensitive consumers, showed a heightened preference for visually distinct and emotionally framed price cues. Despite varying income levels and shopping habits, consistent behavioral patterns were observed in favor of pricing techniques that emphasize value and urgency. The study highlights the psychological impact of pricing on purchasing decisions and provides actionable insights for retailers aiming to boost customer engagement and sales. It contributes to United Nations Sustainable Development Goal (SDG) 8: Decent Work and Economic Growth by promoting responsible business practices and evidence-based marketing strategies in local retail environments. Future researchers are encouraged to examine the demographic nuances of price perception and to explore the evolving role of digital platforms in shaping consumer pricing awareness.